(untitled) (Superficies y Vacío, 2012)
Structural, vibrational and electrical properties of V2O5·nH2O and PEG0.2/V2O5 films as a function of gelation time were studied. The films were sintered by sol-gel using vanadium pentoxide route on glass substrates previously treated. Films were characterized by X-Ray Diffraction, Raman Spectroscopy and the four-point van der Pauw conventional method. The results indicated that when the gelation time of the precursor (V2O5·nH2O) is increased, the crystalline quality, the degree of hydration, and V5+ ion concentration are increased. In the hybrid composite (PEG0.2/V2O5), VO2+ ions act as bonding between the polymer chains, making them more compact to facilitate the mobility of electric charge carriers between vanadium ions. The results showed a semiconductor-metal transition about 34°C, an indirect optical transition (V2O5·nH2O) and a vitreous transition around Tg=-69°C.